(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the situation and some risk behaviors related to hypertension among the Cham people in Ninh Phuoc district, Ninh Thuan province, in 2022. Methods: A cross-sectional study was conducted on 940 Cham people 18 years of age or older at 3 communes in Ninh Phuoc district, Ninh Thuan province, in 2022. Results: Hypertension in the Cham minority group was 38.8% (old hypertension: 27.2%; newly discovered hypertension: 11.6%). The proportion of Cham people with grade 1 hypertension was 69.3%, grade 2 hypertension was 26.4%, and grade 3 hypertension was 4.3%. Some risk behaviors related to hypertension in the Cham ethnic group found in the study included obesity (BMI ≥ 25), alcohol abuse, consuming animal fat habit, and salty eating habits (p < 0.05). Conclusion: It is necessary to step up the work of hypertension detection and development of risk behavioral change community interventions among the Cham people.